Measurement of the X-ray attenuation coefficient of liquid-phase exfoliated WS2 (2024)
Transition metal dichalcogenides (TMDs), compounds with the chemical structure − − where is a transition metal and is a chalcogen, have garnered significant interest due to their unique ability to form two-dimensional (2D) materials. This dimensionality enables TMDs to exhibit extraordinary thermodynamic, electronic, and optical properties, making them versatile candidates for a wide range of applications. Among these, tungsten disulfide (WS2) stands out for its tunable electronic structure and optical behavior, as well as its potential utility in radiation shielding. This study investigates the X-ray attenuation properties of WS2, particularly its ability to serve as a lead-free alternative in shielding applications, given the environmental and health hazards associated with conventional lead-based materials. The WS2 samples were exfoliated using liquid-phase exfoliation (LPE) via lithium ion intercalation, a top-down method aimed at reducing the material to thin layers. Raman spectroscopy corroborated the exfoliation, identifying the vibrational modes 12 and 1 with interpeak frequency shifts indicative of the differences between bulk and exfoliated samples. Scanning electron microscopy (SEM) was used to examine the surface morphology and cross-sectional structures of raw powder and exfoliated samples, enabling the study of physical differences such as layer organization and thickness quantification. Furthermore, to calculate the shielding potential of WS2, X-ray attenuation experiments were conducted using GEM and CdTe Timepix3 detectors. These experiments measured the linear attenuation coefficients as a function of sample thickness and X-ray energy. This study highlights the potential of WS2 as a viable, lead-free material for X-ray attenuation. Its ability to function as a 2D material, coupled with its effectiveness in interacting with X-rays at low energies, positions it as a promising candidate for applications in radiation protection, medical imaging, and other fields requiring efficient, sustainable shielding solutions. These findings lay the groundwork for further exploration of TMDs and other 2D materials as next-generation shielding materials.